THE EFFECT OF STUNTING ON TOOTH ERUPTION AND CARIES STATUS IN CHILDREN AGED 1-3 YEARS (STUDY IN JERUKSARI VILLAGE, TIRTO DISTRICT, PEKALONGAN REGENCY) - Pipit Dias Pitasari; Putri Kusuma; Supartinah Santoso (Journal of Social Research, 2024)
Stunting is a condition of chronic malnutrition. Slow growth in stunted children not only affects height but also affects tooth growth and susceptibility to caries. The aim of this study was to analyze the effect of stunting on tooth eruption and caries status in children aged 1-3 years. This type of research in analytical observational with a cross sectional approach design. The research subjects were stunted children aged 1-3 years. There were 50 children divided into 2 age groups 1-2 years and 2-3 years. Tooth eruption is calculated from the number of teeth that have erupted. The caries status parameters are the def-t index according to WHO (1997) and the caries severity level according to Shimono. Research data was tested using the Mann Whitney Test. Resulted showed that :1) Tooth eruption in stunted children aged 1-3 years was 12.36 + 5.36 less than in non-stunted children 15.54 + 4.02 and showed a significant difference (p<0,005). 2) Caries index (def-t ) in stunted children aged 1-3 years 3.04 + 2.84 higher than the caries index (def-t) in non-stunted children 3.10 + 3.40 aged 1-3 years and shows no significant difference (p> 0.05). 3) The severity of caries in stunted children aged 1-3 years was 33.03 + 10.17 higher than the severity of caries in non-stunted children aged 1-3 years 28.62 + 4.49 and showed a significant difference (p<0,05).